Sexting in Teenagers: The Risk of Revenge Porn Threats in a Victimology Perspective - Nurhadiyanto, Lucky (Universitas Budi Luhur, 2024)
Technology development in the digital era has significantly changed social interaction patterns, including adolescent dating styles. One of the emerging phenomena is sexting, which is sending sexual content through digital media, which often leads to the threat of revenge porn. This study aims to understand the risk of revenge porn victimization in the context of victimology with a qualitative descriptive-exploratory approach. Data were collected through in-depth interviews with victims, observations, and review of related documents. The results of the study indicate that revenge porn is a form of Online Gender-Based Violence (OGV) driven by toxic relationships, where perpetrators use the victim's sexual content as a means of control or revenge. These findings also reveal the importance of digital literacy, legal protection, and the role of psychosocial counseling in preventing and handling revenge porn cases. This study highlights the need for a holistic approach involving legal, social, and educational aspects to protect victims and prevent this phenomenon.